Crack Detection of Power Line Based on Metal Magnetic Memory Non-destructive - Fenglian Niu (Institute of Advanced Engineering and Science, 2014)
Visual inspection method using helicopter equipped with infrared and ultraviolet camera is often employed to check the transmission status of power line, but it is so expensive and unsafe relative to using power line robot to implement crack detection of power line. In this paper a new measuring method is proposed using metal magnetic memory non-destructive (MMMNDT) to to automatically detect defects or abnormal conditions based on a completely autonomous mobile platform capable of a meaningful payload for signal data processing. In this work one kind of brand-new mechanical structure has been designed for inspection robot, and some important parts of the mechanical structure have been fully explained. At the same time, a detection system of the robot has been designed based on MMMNDT. The results of experiments about the crack detection of power line show that the robot can satisfactorily span obstacles automatically and fulfill the specified inspection tasks, experiment results of the detection system verified that this diagnosis system is feasible and can be applied to power line detection.